Role of the bolus degree of structure on the protein digestibility during in vitro digestion of a pea protein‐fortified sponge cake chewed by elderly. Issue 1 (3rd November 2019) - Assad‐Bustillos, Melissa; Palier, Juliette; Rabesona, Hanitra; Choiset, Yvan; Della Valle, Guy; Feron, Gilles
Abstract: This study investigated the digestibility of proteins in a pea protein‐fortified sponge cake, as well as the impact of the degree of structure of the bolus produced by elderly subjects on the digestibility of proteins by combining ex vivo and in vitro approaches via the standardized protocol INFOGEST. The sponge cakes were consumed by a group of 20 elderly subjects with contrasting physiology, their boli were recovered just before swallowing, and their apparent viscosity was measured to delineate the bolus degree of structure. According to this criterion, two pools were formed with boli from subjects selected at the extremes: low viscosity and high viscosity, with apparent viscosity values (at 120 s −1 ) of 124 ± 18 and 208 ± 19 Pa s, respectively. The sponge cakes and the two pools underwent in vitro digestion. Protein hydrolysis kinetics was followed by measuring the released primary amino groups (NH2 ) and by sodium‐dodecyl‐sulfate polyacrylamide gel electrophoresis at different time points. For all samples, the representative bands of pea proteins disappear gradually during digestion, accompanied by the appearance of bands indicating the presence of proteins with M W  < 15 kDa. In addition, the NH2 concentrations increase over time and do not differ between sponge cake and pea protein isolate. Moreover, the degree of structure of the food bolus has no significant effect on the concentration of NH2 released. These results showed that pea proteins in a fortified sponge cake are bioaccessible under standardized conditions and that the degree of structure of the bolus did not influence protein digestibility for these foods.